The Impact of Attitude and Knowledge on Consent Decisions for Cataract Surgery: A Study at Siloam Hospitals Lippo Village, Building B - Wibisono, Atria Puspitaloka; Irma, Josiah; Rizki, Saraswati Anindita (Medicinus, 2025)
Introduction: Cataracts account for 77.7% of blind cases in Indonesia, indicating that many cataract patients have not had surgery. Low levels of knowledge, attitude, and decision-making among cataract patients regarding surgery may limit the number of procedures performed in Indonesia. Therefore, this study aims to assess cataract patients’ knowledge, attitude, and decision-making concerning surgery at Siloam Hospitals Lippo Village in Tangerang. Objective: To determine the relationship between knowledge, attitude, and decision-making regarding cataract surgery among Siloam Hospitals Lippo Village Building B patients. Methods: This cross-sectional study involves 64 cataract patients visiting Siloam Hospitals Lippo Village Building B. The collected data were analysed using SPSS Statistics bivariate analysis. Results: Out of the 64 respondents, 7 (10.9%) demonstrated low knowledge, 4 (6.3%) displayed a negative attitude, and 4 (6.3%) indicated unwillingness to undergo surgery. A significant relationship exists between knowledge and attitude, attitude and decision, and knowledge and decision regarding cataract surgery, with a p-value of 0.000 as determined by the Pearson Chi-Square test. Conclusion: A significant relationship exists between knowledge, attitude, and the decision to undergo cataract surgery.